Manual of professional practice for civil engineers (Quezon City, Philippines : The National Office and Library, 2001)
This manuals contains information that a civil engineer in any position of engagement or employment may find useful to know and to follow.
Section 1. The practice of civil engineering -- Section 2. Classification of engineering services -- Section 3. The selection of the civil engineer -- Section 4. Charging for civil engineering services -- Section 5. Total project cost.
Keywords: CIVIL ENGINEER -- HANDBOOKS, MANUALS, ETC